2006
DOI: 10.1071/ar05180
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield and milk composition from grazing primiparous non-dairy crossbred ewes

Abstract: Milk production and milk composition were studied in 520 primiparous Merino crossbred ewes that were the progeny of 30 sires from several maternal crossing breeds including Border Leicester, Coopworth, Finnsheep and East Friesian. The ewes were born in 3 years (1997, 1998, and 1999), with 3 sires used in every year to provide genetic links. The crossbred ewe lambs were randomly assigned to autumn or spring joining groups and mated to Poll Dorset rams to lamb at 12 or 19 months of age. Ewes were milked on 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
2
20
3
Order By: Relevance
“…Holst and Hall (1994) reported that milk yield measured at an average age of 4 weeks was significantly related to single lamb weights at 8 and 12 weeks and at weaning. The lamb growth rates in Period 1 from the five breed groups were similar in ranking to the ranking of the ewes for 21-day milk yield reported by Morgan et al (2006). The low growth rates of lambs from Finnsheep cross ewes in Period 1 is associated with their low milk yield.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Holst and Hall (1994) reported that milk yield measured at an average age of 4 weeks was significantly related to single lamb weights at 8 and 12 weeks and at weaning. The lamb growth rates in Period 1 from the five breed groups were similar in ranking to the ranking of the ewes for 21-day milk yield reported by Morgan et al (2006). The low growth rates of lambs from Finnsheep cross ewes in Period 1 is associated with their low milk yield.…”
Section: Discussionsupporting
confidence: 65%
“…In this experiment there was a growth rate advantage of the Border Leicester over the Finnsheep breed group in Period 1 (30 g/day), although it was negligible in Period 2 (1 g/day). The East Friesian cross ewes had similar 21-day milk yield (2.19 v. 2.16 kg/day, not significant) to the Border Leicester cross ewes (Morgan et al 2006) and their lambs had similar growth rates to those from the Border Leicester ewes (305 v. 309 g/day, not significant) in Period 1. However, in Period 2 lambs born to East Friesian cross ewes had significantly higher growth rates than all other lambs.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Nonetheless the liveweight change of the ewe during pregnancy was the next most important influence on weaning weight and more important than changes in ewe liveweight during lactation. This lesser impact of ewe liveweight change during lactation on weaning weight was expected as ewes preferentially partition nutrients to milk production rather than body reserves during lactation (Morgan et al 2006). The prediction of growth rate and weaning weight of progeny from feed on offer during lactation and ewe liveweight profile to lambing were consistent across two seasons at each of two sites.…”
Section: Discussionmentioning
confidence: 68%
“…By contrast, Ochoa et al (2007) reported that Rambouillet ewes that gave birth to single lambs produced milk with a higher concentration of fat, protein, and total solids. Morgan et al (2006) and Afolayan et al (2009) did not find effect of litter size on milk protein, fat, and lactose content. Milk protein content was lower in Tsigai and Valachian ewes giving singles birth singles, whereas in Lacaune ewes, no difference in protein content between the ewes lambing singles or multiples was found (Oravcová et al 2007).…”
Section: Milk Compositionmentioning
confidence: 59%